Georgia Architectural and Historic Properties Survey of 213 Walnut St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 213 Walnut St., Valdosta, Ga., December 1980. One story saddlebag house. Rectangular plan. Gabled, tin roof. Shed porch with tapered brick posts. Double hung sash windows with 2/2 lights. Set on brick piers. Asbestos siding. Good condition. Date of Construction: App. 1915-1920. Significant as part of a potential N.R. district which would cover about 4 or 5 blocks.
Georgia Architectural and Historic Properties Survey of 213 Walnut St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.4 MB (83,266,085 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)